Interactional Communication Between Teacher and Students to Improve the Quality of Learning At the Mutiara Hati Magelang Special School - Arum Marwati; Safrina Jasmine; Widhihatmini Widhihatmini; Rahmat Rian Hidayat; Ardian Setio Utomo (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This research is motivated by the importance of interactional communication in building effective relationships between teachers and students in Special Needs Schools (SLB), particularly at Mutiara Hati Special Needs School in Magelang. Unresponsive and one-way communication often becomes an obstacle in creating optimal learning quality for students with special needs, especially students who experience verbal barriers and social development disorders. In this context, this research aims to identify teacher interactional communication practices that can encourage increased student participation and motivation in learning. This research uses the interactional communication theory of Schramm and Budianto, which includes five leading indicators: response, openness, trust, empathy, and support. This study uses a descriptive qualitative approach with data collection methods through in-depth interviews, participant observation, and documentation. The primary informants consisted of three teachers at Mutiara Hati Special Needs School who had direct experience interacting with students with special needs. The study results indicate that interactional communication practices that prioritize empathy and openness, as well as adaptive verbal and nonverbal responses to the unique needs of each student, contribute significantly to increasing learning motivation, self-confidence, and learning quality. Teachers who demonstrate emotional understanding and use non-verbal approaches such as gentle facial expressions and light touch have been shown to create a more supportive and inclusive classroom climate. Effective interactional communication is a tool for conveying messages and a medium for building deep psychological connections between teachers and students. This study also recommends interactive communication training for special needs teachers as a sustainable strategy to improve the quality of inclusive education in Indonesia.